Identifying motivational profiles among VET students : differences in self-efficacy, test anxiety and perceived motivating teaching - Cents-Boonstra, Miriam [Verfasser]; Lichtwarck-Aschoff, Anna [Verfasser]; Denessen, Eddie [Verfasser]; Haerens, Leen [Verfasser]; Aelterman, Nathalie [Verfasser] (My University, 2019)
"There are indicators that a substantial number of students in vocational education and training (VET) experience problems with successfully building their careers. This is often attributed to VET students’ motivation. The present study provides insight into VET students’ motivational profiles based on self-determination theory. Additionally, differences between those motivational profiles in terms of self-efficacy, test anxiety and perception of motivating teaching were investigated. The study involved 195 VET students, from one VET college in the Netherlands. Using latent profile analyses, four motivational profiles were identified that differed with respect to quality and quantity of motivation. Profiles with higher quality (25%) and higher quantity (27%) of motivation were related to higher levels of self-efficacy and perceived motivating teaching compared to profiles with low quantity (7%) or low quality (41%) of motivation. Furthermore, students in the profile with high-quality motivation reported the lowest levels of test anxiety. Additionally, our findings suggest there is indeed a relatively large group of VET students (48%) who actually experience motivational problems. Practical implications and directions for future research are discussed." (author's abstract ; BIBB-Doku)
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); Berufsverlauf; Ausbildungsabbruch; Selbstwirksamkeit; Prüfungsangst; Ausbildungsmotivation; Niederlande